(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Water samples collected from fifteen hand dug wells in November (dry season), 2011 and July (Wet season), 2012 using random sampling technique. In situ parameters were measured for pH, electrical conductivity, total dissolved solids using portable meters. Heavy metals were analyzed for; Fe, Cu, Zn, Cd, Pb, and Cr using Atomic Absorption Spectrophotometer (AAS). The study aimed at examining the spatial variations in groundwater quality around dumpsite in Igando using paired sample T-test statistical technique. The result shows that the measured pH values were below the minimum WHO standard for drinking water quality in wet and dry seasons in about73.3% and 26.7% respectively. Also, approximately, 13.3% of EC, and 6.7% exceeded the prescribed standard limit of WHO in dry and wet seasons respectively. Concentration of Fe exceeded drinking water quality in all the sampling locations during wet season and only about 46.7% in dry season. Pb, Zn, and Cu exceeded WHO limit in about 86.7%, 80%, and 26.7% respectively in dry season. Concentration of Pb, Cd , Cu and Cr were under detection limit in all the locations except at locations G2 for Cu in wet season. The paired samples statistics and correlation revealed that the mean values of all the parameters were higher in dry season with the exception of Fe. No significant correlations exist among the paramet er for both seasons at p<0.05. The paired T-test show significant seasonal variations among four heavy metals including Fe, Cd, Pb and Zn.The study concluded that, samples in dry season are of low quality compared to wet. The study recommends public enlightenment on solid waste disposal, controlled anthropogenic activities, and treatment /recycling of waste to prevent heavy metal from leaching unto the sub-surface. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22063 J. Environ. Sci. & Natural Resources, 6(1): 179-186 2013